1976
DOI: 10.1148/119.1.209
|View full text |Cite
|
Sign up to set email alerts
|

Time, Dose and Volume Factors in Interstitial Radium Implants of Carcinoma of the Oral Tongue

Abstract: In a retrospective computer dosimetry analysis of 58 patients with carcinoma of the oral tongue treated with interstitial radium implants alone or in combination with external irradiation, dose and volume appear to be the most important factors in both local control and the incidence of necrosis; in the dose rate range commonly used in clinical interstitial radiotherapy, dose rate has no significant effect. The optimal minimum tumor doses for local control vary with the size of the primary lesion: 6,000 rads f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The largest series is that of Pierquin et al,17 who have evaluated local control of lesions up t o 4 cm in size, reporting in 153 patients an astonishing 95% local control at six months and at four years (metastatic disease limited the overall four-year survival to 50%). Also satisfactory is a control rate of 76% in 50 patients with lesions of less than 4 cm, and an overall control rate of 71% in 58 patients, reported by Fu et al 7 Delclos et a13 have reported 82% (28/34) local control with lesions of less than 4 cm, and 80% (37/46) overall control. At the University of Southern California (USC) Medical Center, a total of 21 patients with oral-cavity lesions were treated and followed for a minimum of two years; 87% (7/8) of these patients with lesions smaller than 4 cm are living without tumor, and 71% (10/14) with lesions larger than 4 cm are controlled at two years.…”
Section: Resultsmentioning
confidence: 81%
“…The largest series is that of Pierquin et al,17 who have evaluated local control of lesions up t o 4 cm in size, reporting in 153 patients an astonishing 95% local control at six months and at four years (metastatic disease limited the overall four-year survival to 50%). Also satisfactory is a control rate of 76% in 50 patients with lesions of less than 4 cm, and an overall control rate of 71% in 58 patients, reported by Fu et al 7 Delclos et a13 have reported 82% (28/34) local control with lesions of less than 4 cm, and 80% (37/46) overall control. At the University of Southern California (USC) Medical Center, a total of 21 patients with oral-cavity lesions were treated and followed for a minimum of two years; 87% (7/8) of these patients with lesions smaller than 4 cm are living without tumor, and 71% (10/14) with lesions larger than 4 cm are controlled at two years.…”
Section: Resultsmentioning
confidence: 81%
“…Although Korb et al (29) found no difference in local control rate between patients with TI -2 lesions treated with versus without implant, a majority of authors have reported that a high dose brachytherapy is necessary for securing a good local control (3,7,9,30). For patients treated with combined external and interstitial irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Results of radiation therapy for carcinoma of the tongue are related to the size of the primary lesion and [4,[6][7][8][9][10]. Many patients with advanced tumours are unable to tolerate radical attempts at cure by any modality.…”
Section: Discussionmentioning
confidence: 99%